Knockdown of tgfb1a partially improves ALS phenotype in a transient zebrafish model - Gonzalez, David; Cuenca, Xiomara; Allende, Miguel L. (Frontiers in Cellular Neuroscience, 2024)
Amyotrophic lateral sclerosis (ALS) corresponds to a neurodegenerative disorder marked by the progressive degeneration of both upper and lower motor neurons located in the brain, brainstem, and spinal cord. ALS can be broadly categorized into two main types: sporadic ALS (sALS), which constitutes approximately 90% of all cases, and familial ALS (fALS), which represents the remaining 10% of cases. Transforming growth factor type-β (TGF-β) is a cytokine involved in various cellular processes and pathological contexts, including inflammation and fibrosis. Elevated levels of TGF-β have been observed in the plasma and cerebrospinal fluid (CSF) of both ALS patients and mouse models. In this perspective, we explore the impact of the TGF-β signaling pathway using a transient zebrafish model for ALS. Our findings reveal that the knockdown of tgfb1a lead to a partial restoration prevention of motor axon morphology abnormalities and locomotor function deficits in a transient ALS zebrafish larvae model at 48 hours post-fertilization (hpf). In this context, we delve into the proposed distinct roles of TGF-β in the progression of ALS. Indeed, some evidence suggests a dual role for TGF-β in ALS progression. Initially, it seems to exert a neuroprotective effect in the early stages, but paradoxically, it may contribute to disease progression in later stages. Consequently, we suggest that the TGF-β signaling pathway emerges as an attractive therapeutic target for treating ALS. Nevertheless, further research is crucial to comprehensively understand the nuanced role of TGF-β in the pathological context.Con formato: Resaltar